The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-853709/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of Quercetin Therapeutic Targets for Alzheimer Disease and type 2 Diabetes Mellitus

Abstract: Quercetin has demonstrated antioxidant, anti-inflammatory, hypoglycemic, and hypolipidemic activities, suggesting therapeutic potential against type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD). In this study, potential molecular targets of quercetin were first identified using the Swiss Target Prediction platform and pathogenic targets of T2DM and AD were identified using Online Mendelian Inheritance in Man (OMIM), DisGeNET, TTD, DrugBank, and GeneCards databases. The 95 targets shared among querce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…[44] Multiple AD-related network pharmacology literature reported that AKT1 plays a crucial role in AD. [43][44][45][46][47] IL6, TNF, and IL1B are often used as proinflammatory markers in AD. [48,49] The remaining core targets are all playing essential roles in AD.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Multiple AD-related network pharmacology literature reported that AKT1 plays a crucial role in AD. [43][44][45][46][47] IL6, TNF, and IL1B are often used as proinflammatory markers in AD. [48,49] The remaining core targets are all playing essential roles in AD.…”
Section: Discussionmentioning
confidence: 99%